Fiction et vérité - Sabot, Philippe (Itinerari, 2024)
The concept of fiction is frequently associated with the notion of truth. This association can be observed in two distinct approaches: firstly, fiction is often seen as a means of challenging the very notion of truth, particularly in instances where it is perceived to deceive or prove untrue in its essence. Secondly, fiction is frequently regarded as a system of verisimilitude, characterised by a specific order of illusion or fiction. This approach emphasises the appeal of fiction and attempts to explain, if not justify, its allure. This article will examine whether this complex relationship with the concept of truth enables us to define fiction in a meaningful way. Furthermore, it will investigate whether, when considering this criterion of truth, it is beneficial, or even essential, to make a more detailed distinction between the various forms of fiction, of which literary fiction is only one example. We will then inquire whether it is still feasible to imbue this particular area of fiction with an intrinsic capacity for truth, one that transcends the epistemological concerns surrounding the acquisition of knowledge through controlled and verifiable means. In this sense, we will consider the ethical implications of learning about the world and the relationships that shape our understanding of it, including our relationship with ourselves and with others.